An Analysis of Short Story The Little Match Girl by Hans Christian Andersen in Semantics Perspective - Ni Wayan Swarniti (CV. Tirta Pustaka Press, 2024)
This research aims to analyze the antonymy and synonym existed in a short story titled “The Little Match Girl” by Hans Christian Andersen. This research employs a qualitative semantics analysis to investigate the underlying meanings and implications of the language used in